Molecular Characterization of dax1 and SF‐1 and Their Expression Analysis During Sex Reversal in Spotted Scat, Scatophagus argus. Issue 1 (February 2015) - Chen, Jianhua; He, Maoxian; Yan, Binlun; Zhang, Junbin; Jin, Sichen; Liu, Lu
Abstract The nuclear receptors dax1 and SF‐1 play important and antagonistic roles in gonad differentiation in mammals. To study their potential functions in teleost fish, the full‐length cDNAs of dax1 and SF‐1 were cloned and characterized from spotted scat. Their expression patterns in adult tissues and juveniles treated with 17α‐methyltestosterone (MT) and their gonadal histological changes were investigated, respectively. The tissue‐specific expression results showed that dax1 was abundantly expressed in the gonads, spleen, brain, and intestine. SF‐1 was preferentially expressed in the gonad and spleen. Histological results showed that sex reversal could be induced by MT, and the degenerating oocytes and proliferations of spermatogonia were observed in gonad. At the beginning of sex reversal (40 d after treatment), the mRNA level of dax1 significantly increased, and the transcript level of SF‐1 mRNA was inhibited at the point of 20 d following treatment with MT. Our results suggested that masculinization could be induced by MT treatment in spotted scat, and MT could upregulate the dax1 expression, whereas it downregulates the expression of SF‐1, which implied that dax1 and SF‐1 might be involved in the gonad development from female to male and there was an antagonistic effect between dax1 and SF‐1.